EXPLORING THE RELATIONSHIP BETWEEN SELF-EFFICACY AND SELF MOTIVATION AMONG WOMEN’S FUTSAL ATHLETE STUDENT - Salsabillah, Insyafadya; Fitri, Mustika; Hamidi, Ahmad; Apriady, Hilmy; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
Achieving peak athletic performance in sports requires a combination of physical prowess and psychological factors, including self-efficacy and self-motivation. This study investigate these variables among professional female futsal athletes in Indonesia, examining their interrelationship and the influence of team goals and backgrounds. The sample consists of 28 players each from Muara Enim United, targeting league victory, and Alive FC, a newly promoted team focused on avoiding relegation. Data collection utilized the the Athlete Self-Efficacy Scale (ASES) and Self-Motivation Scale II (SMS-II), administered during pre-season training via online surveys. Descriptive statistics reveal higher mean scores for self-efficacy and self-motivation in Muara Enim United compared to Alive FC, supporting the hypothesis that team objectives impact these psychological attributes. However, correlation analysis indicates no significant relationship between self-efficacy and self-motivation within either team, contrary to initial expectations. This underscores the complexity of motivational dynamics in sports, influenced by multifaceted factors beyond individual psychological traits. The findings suggest that while self-efficacy and self-motivation play pivotal roles in sports performance, their relationship may vary across different competitive contexts and team environments. This study contributes to the understanding of athlete motivation in professional sports and highlights the need for tailored psychological interventions to explore additional variables and contexts that may influence the interplay between self-efficacy, self-motivation, and athletic achievements in diverse sporting disciplines.